1989
DOI: 10.1161/01.cir.79.6.1180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperhomocyst(e)inemia in patients with peripheral arterial occlusive disease.

Abstract: A micromethod adapted for automated determinations was used to measure basal plasma levels of homocyst(e)ine [H(e)J. These levels included the sum of free and bound forms of homocysteine, its disulfide oxidation product, homocystine, and the homocysteine-cysteinemixed disulfide. Two groups of subjects were studied: apparently healthy individuals (n = 103) and patients with peripheral arterial occlusive disease (PAOD) (n= 47). Because age in PAOD patients was higher than in control subjects, the control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
193
3
6

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(210 citation statements)
references
References 44 publications
5
193
3
6
Order By: Relevance
“…Our previous studies showed that plasma homocysteine concentrations in rats fed a methionine diet are increased by Ϸ3-fold, 10,11 reaching a concentration similar to that shown to be associated with an increased risk of vascular disease in humans. 1,4,5,18 In these studies, we demonstrated that acetylcholine and histamine-induced, NO-mediated endothelial dilations are reduced in skeletal muscle arterioles of HHcy rats. 10 In addition, bradykinin induces an enhanced constriction of HHcy arterioles via increased TXA 2 production in the endothelium.…”
Section: February 2001mentioning
confidence: 81%
See 1 more Smart Citation
“…Our previous studies showed that plasma homocysteine concentrations in rats fed a methionine diet are increased by Ϸ3-fold, 10,11 reaching a concentration similar to that shown to be associated with an increased risk of vascular disease in humans. 1,4,5,18 In these studies, we demonstrated that acetylcholine and histamine-induced, NO-mediated endothelial dilations are reduced in skeletal muscle arterioles of HHcy rats. 10 In addition, bradykinin induces an enhanced constriction of HHcy arterioles via increased TXA 2 production in the endothelium.…”
Section: February 2001mentioning
confidence: 81%
“…Key Words: homocysteine Ⅲ arteriole Ⅲ flow-induced response Ⅲ endothelium Ⅲ nitric oxide Ⅲ thromboxane A 2 I ncreasing epidemiological and experimental evidence suggests that an elevated plasma level of homocysteine is associated with the development of peripheral arterial disease. [1][2][3][4][5] Homocysteine is a sulfur-containing amino acid that is formed during the metabolism of the essential amino acid methionine. 4 Plasma homocysteine concentration can be increased through alterations in genetic and nutritional factors, such as various enzyme (cystathione-␤-synthase, methyltetrahydrofolate reductase) abnormalities and deficiency of vitamins (folic acid, cyanocobalamin, pyridoxal phosphate), all of which participate in the metabolism of homocysteine and methionine (for further references, see Lentz et al 4 ).…”
mentioning
confidence: 99%
“…22,23 Total plasma cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides were measured using methods established by the Lipid Research Centers and standardized by the Centers for Disease Control and Prevention, Atlanta, Ga. 24 …”
Section: Other Assaysmentioning
confidence: 99%
“…Key Words: homocysteine Ⅲ methionine synthase Ⅲ methylenetetrahydrofolate reductase Ⅲ genetics R ecent reports indicate that even modest increases in plasma homocyst(e)ine levels can lead to an increased risk of occlusive vascular disease. [1][2][3][4][5][6][7][8][9] Homocysteine is a sulfur amino acid generated as an intermediate product in methionine metabolism and occurs at the intersection of 2 metabolic pathways, remethylation and transsulfuration. These pathways are known to be regulated by 3 key enzymes: cystathionine ␤-synthase, 5-methyltetrahydrofolate:homocysteine methyltransferase (methionine synthase), and 5,10-methylenetetrahydrofolate reductase (MTHFR), as well as by the cofactors folate, vitamin B 6 , and vitamin B 12 .…”
mentioning
confidence: 99%